2007
DOI: 10.1677/joe-07-0003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endocrine genes in zebrafish larvae in response to environmental salinity

Abstract: We tested the capability of the endocrine system in zebrafish to respond to environmental salinity challenges during larval stages. We reveal that the zebrafish larvae have a system in which several endocrine genes, including atrial natriuretic peptide (anp), renin, prolactin, growth hormone ( gh) and parathyroid hormone 1 (pth1), respond at the transcription level to changes in environmental salinity and that the responses are gene specific. Both anp and renin are upregulated in larvae raised in dilute freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…Salinity solutions were prepared as previously described (24,60). Captopril (C4042, Sigma-Aldrich) was administered at 0.1 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity solutions were prepared as previously described (24,60). Captopril (C4042, Sigma-Aldrich) was administered at 0.1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…If functionally conserved, the fish RAS may also function in ion homeostasis and development. The zebrafish pronephros is functional from 76 hours postfertilization (hpf) (13), and recent studies in fish have suggested that larval renin (24) and the RAS (35) may be involved in ion homeostasis. Canonical ANG II-mediated Na ϩ uptake via aldosterone activation of the epithelial Na ϩ channel in the distal nephron of mammals may differ in zebrafish, which lack aldosterone synthase.…”
mentioning
confidence: 99%
“…The physiological role of the RAS in fish is not completely understood. Nevertheless, increasing evidence suggests that the RAS is involved in osmoregulation (Fuentes and Eddy, 1997;Hoshijima and Hirose, 2007;Kumai et al, 2014a;Smith et al, 1991). It is well documented that ANG-II promotes drinking in euryhaline fish (Beasley et al, 1986;Carrick and Balment, 1983;Fuentes and Eddy, 1996;Kobayashi et al, 1983), potentially increasing salt absorption from the gut.…”
Section: Angiotensin IImentioning
confidence: 99%
“…Smith et al (1991) reported a decline in plasma renin activity in freshwateracclimated rainbow trout fed with a salt-enriched diet, suggesting a possible role for ANG-II in the regulation of salt balance in freshwater fish. Subsequently, Hoshijima & Hirose (2007) reported an increase in renin mRNA expression during acclimation of zebrafish to ion-poor water (20-fold dilution of the control water), suggesting a role of the RAS in promoting salt absorption. Despite these studies, the question of whether the RAS promotes salt uptake in freshwater fish remains unexplored.…”
Section: Introductionmentioning
confidence: 99%